THE INFLUENCE OF DEBT COVENANT, PROFITABILITY, BONUS PLAN, AND EXCHANGE RATE ON TAX AVOIDANCE WITH TRANSFER PRICING AS AN INTERVENING VARIABLE IN RAW GOODS SECTOR COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Apriyanto, Vito; Leon, Hengky; Haryadi, Dedi (LPPM Universitas Bina Bangsa, 2024)
In companies operating in the Raw Goods Sector that are publicly traded on the Indonesian Stock Exchange, the objective of this research is to determine how debt covenants, profitability, bonus plans, and exchange rates influence transfer pricing. Furthermore, the study seeks to ascertain the impact of transfer pricing, equity markets, debt covenants, profitability, and compensation schemes on tax evasion within the Raw Materials Sector of Indonesian Stock Exchange-listed companies. The research methodology employed in this study is associative research. The subject of investigation is the raw materials industry on the Indonesia Stock Exchange throughout the period from 2018 to 2022. The population for this study consists of 96 companies registered on the Indonesia Stock Exchange in the primary consumer products industry, spanning from 2018 to 2022. The research employed a purposive sampling strategy. This research consisted of a sample size of 23 firms. The data analysis technique is facilitated by the utilization of a specific tool, namely Statistical Product and Service Solution (SPSS) version 26. The research findings indicate that the variables of debt covenant, bonus plan, exchange rate, and transfer pricing do not have any impact on tax avoidance. However, profitability is found to have a negative influence on tax avoidance. Debt covenant, profitability, bonus plan, and exchange rate do not impact transfer price. In addition, transfer pricing is unable to reconcile debt covenants, profitability, compensation schemes, and the impact of exchange rates on tax evasion.. Indonesia as a country that has many companies that have been successful at the national and international levels can increase sources of state revenue. As the company's profit rises, the corresponding tax payment also grows. This forms the basis for companies to employ tax evasion tactics in order to reduce their tax obligations. This study investigates the factors that influence tax evasion